ANALISIS KREATIVITAS SISWA DALAM IMPLEMENTASI P5 PEMBUATAN BATIK JUMPUTAN DI SD NEGERI 2 SUNGAI BELIDA - Indah Ani Satul Luthfia; Linda Lia; Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze students' creativity in the implementation of the Strengthening the Profile of Pancasila Students Project (P5) through batik jumputan-making activities at SD Negeri 2 Sungai Belida. Creativity is a key aspect in developing students' character and competence in the Merdeka Curriculum. This research used a descriptive qualitative approach with data collection techniques including observation, interviews, and questionnaires. The research subjects were fourth-grade students who participated in the P5 activity, as well as the teacher who guided the project. The results showed that the P5 activity involving batik jumputan effectively encouraged and enhanced students' creativity. This was evident from their ability to think creatively, work collaboratively, express their talents, and use imagination in creating unique batik patterns. Students showed high enthusiasm, the courage to try new ideas, and the ability to cooperate well in teams. In addition to producing aesthetically valuable works, the activity also fostered Pancasila values such as independence, teamwork, and creativity. Therefore, the implementation of P5 activities based on local wisdom, such as batik jumputan, can serve as an effective learning method to explore and develop students’ creative potential holistically.